Integration in Early Grade Instruction: Effects on Academic Achievement of Grade 1 Students - Hinggangan, Manilyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
In today's world, technology is a key player in education, changing how teachers teach and students learn. This study examined how modern technology affects teaching Grade 1 Science students in Bambang District, Nueva Vizcaya, during the 2025–2026 school year. It focused on the availability of tech tools, the level of teachers’ technological skills, the effectiveness of tech in the classroom, and the challenges teachers face when using tech in science lessons. This study used a descriptive quantitative research design and gathered data from 20 Grade 1 teachers using a specially designed questionnaire. Frequency count, percentage, weighted mean, standard deviation, and ranking were employed to analyze the data. The findings showed that teachers generally found modern technology to be effective in enhancing science instruction. The overall average weighted mean indicated that the respondents strongly agreed that technology boosts students' participation, motivation, engagement, and understanding of science concepts. Teachers also showed proficiency in using technological tools during lessons. However, they faced challenges such as poor internet connection, lack of technology resources, limited technical skills, and insufficient training opportunities. The study concluded that modern technology positively impacts teaching and learning in Grade 1 Science. Therefore, schools should continue to improve technology integration by providing sufficient resources, stable Internet, and ongoing teacher training to enhance the quality of science education and students’ learning experiences.
Keywords: Grade 1 Pupils; Modern Technology; Science Education; Technology Integration; Teaching Effectiveness